Popular wood and sugarcane bagasse biochars reduced uptake of chromium and lead by lettuce from mine-contaminated soil - Khan, Amir Zeb (Environ Pollut, 2020)
As a result of metal mining activities in Pakistan, toxic heavy metals (HMs) such as chromium (Cr) and lead (Pb) often enter the soil ecosystem, accumulate in food crops and cause serious human health and environmental issues. Therefore, this study examined the efficacy of biochar for contaminated soil remediation. Poplar wood biochar (PWB) and sugarcane bagasse biochar (SCBB) were amended to mine-contaminated agricultural soil at 3% and 7% (wt/wt) application rates. Lactuca sativa (Lettuce) was cultivated in these soils in a greenhouse, and uptake of HMs (Cr and Pb) as well as biomass produced were measured. Subsequently, health risks were estimated from uptake data. When amended at 7%, both biochars significantly (P<0.01) reduced plant uptake of Cr and Pb in amended soil with significant (P<0.01) increase in biomass of lettuce as compared to the control. Risk assessment results showed that both biochars decreased the daily intake of metals (DIM) and associated health risk due to consumption of lettuce as compared to the control. The Pb human health risk index (HRI) for adults and children significantly (P<0.01) decreased with sugarcane bagasse biochar applied at 7% rate relative to other treatments (including the control). Relative to controls, the SCBB and PWB reduced Cr and Pb uptake in lettuce by 69%, 73.7%, respectively, and Pb by 57% and 47.4%, respectively. For both amendments, HRI values for Cr were within safe limits for adults and children. HRI values for Pb were not within safe limits except for the sugarcane bagasse biochar applied at 7%. Results of the study indicated that application of SCBB at 7% rate to mine impacted agricultural soil effectively increased plant biomass and reduced bioaccumulation, DIM and associated HRI of Cr and Pb as compared to other treatments and the control.